Expresión musical y expresión corporal en niños de la Institución Educativa Inicial N° 743 del distrito de San Pablo 2021 - Manihuari Upiachihua, Irene (2023)
The results that respond to the objectives of the study are explicitly summarized, the main objective being to relate musical expression and corporal expression in five-year-old children of the initial educational institution No. 743 in the district of San Pablo in the year 2021. For this purpose, the type of relational research was used, in addition to having a cross-sectional, bivariate, and field design. As a unit of analysis, the five-year-old child was taken and the population was 50, who, when applying the census method, also became the sample. The observation technique was used with observation guides as data collection instruments, which were validated by experts. It is concluded that Spearman's rho correlation coefficient = 0.299**; p=0.035 < 0.005, shows a significant direct relationship between musical expression and body expression in five-year-old children from the initial educational institution No. 743 in the district of San Pablo.